Whether technology and Human Resources competencies supported by periodic audits can improve Village Fund Financial Accountability - Haliah; Widyantono Arif; Muh Alief Fahdal Imran; Hasnawiya Hasan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The purpose of this study has an orientation to analyze the effect of the use of Information Technology, Human resources competence, and periodic audits that are moderated in the realization of Financial Accountability Bottopenno village fund in Majauleng District Wajo. In order to achieve the formulated research orientation, this study uses quantitative research with descriptive paradigm. Sources of data used are primary data obtained through the distribution of questionnaires and secondary data obtained through the internet and district data. Methods of analysis exist using multiple linear regression and Moderated Regression Analysis (MRA). The results revealed that the use of Information Technology and Human Resource competence has a positive and significant influence on the financial accountability of the village fund. Periodic audits can also be a moderator between the positive and significant influence of information technology utilization and Human Resource competence on financial accountability of village funds.